Ответы и объяснения

2013-12-12T21:30:18+04:00
В) sin^2x - 2sinx*cox = 3cjs^2x
sin^2x - 2sinx*cox - 3cjs^2x = 0
Делим всё на cos^2x:
tg^2x - 2tgx - 3 = 0 , tgx=t
t^2 - 2t - 3 = 0
Д=16=4^2
t1=3
t2= -1

tgx1=3
x1=+-arctg3+ \pi n, n∈Z

tgx2=-1
x2=-arctg1+ \pi n, n∈Z
x2=- \pi /4 +  \pi n, n∈Z

г) 3cos^2x = 4sinx*cosx - sin^2x
3cos^2x - 4sinx*cosx + sin^2x =0
Делим всё на cos^2x:
3 - 4tgx + tg^2x = 0, tgx=t
 t - 4t + 3 = 0
Д=4 = 2^
t1= 1
t2 =4

tgx1=1
x1=+-arctg1 +  \pi n, n∈Z
x1=+- \pi /4 +  \pi n, n∈Z

tgx2=4
x2=+-arctg4 +  \pi n, n∈Z